Elementary topology: problem textbook - Viro, O. Ya.; Ivanov, O. A.; Netsvetaev N. Yu.; Kharlamov V. M. (Providence, Rhode island American Mathmetical Society, 2008)
The book is tailored for the reader who is determined to work actively. The proofs of theorems are separated from their formulations and are gathered at the end of each chapter. This makes the book look like a pure problem book and encourages the reader to think through each formulation. A reader who prefers a more traditional style can either find the proofs at the end of the chapter or skip them altogether. This style also caters to the expert who needs a handbook and prefers formulations not overshadowed by proofs. Most of the proofs are simple and easy to discover.
Keywords: Mathematics; Topology-Textbooks; Algebraic topology